2016
DOI: 10.1155/2016/3897064
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Local Sand on the Physicomechanical Comportment and Durability of High Performance Concrete

Abstract: This research consists of incorporating the crushed sand (CS) in the composition of a concrete and studies the effect of its gradual replacement by the sand dune (SD) on sustainability of high performance concrete (HPC) in aggressive environments. The experimental study shows that the parameters of workability of HPC are improved when the CS is partially replaced by the SD (<2/3). However, a high content of SD (>1/3) additional quantities of water is needed to meet the workability properties. The mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…On the contrary, if DS content is less than 30%, the absorption is not affected. In the same way, Tebbal and Rahmouni (2016) have shown the positive impact of partial replacement of DS by CS (combination of 1/3 DS with 2/3 CS) in High-performance concrete (HPC) concrete, which leads to improve the mechanical strength of concrete immersed in aggressive environment. Mortars and concretes made with DS are more porous than those made with RS, which facilitates the penetration of aggressive chemical solutions and leads to reduce the grip properties and mechanical characteristics of concretes.…”
Section: Introductionmentioning
confidence: 86%
“…On the contrary, if DS content is less than 30%, the absorption is not affected. In the same way, Tebbal and Rahmouni (2016) have shown the positive impact of partial replacement of DS by CS (combination of 1/3 DS with 2/3 CS) in High-performance concrete (HPC) concrete, which leads to improve the mechanical strength of concrete immersed in aggressive environment. Mortars and concretes made with DS are more porous than those made with RS, which facilitates the penetration of aggressive chemical solutions and leads to reduce the grip properties and mechanical characteristics of concretes.…”
Section: Introductionmentioning
confidence: 86%
“…al.14 developed set of coefficients to address the issue with respect to workability of concrete. Several other studies report use of waste products as replacement of the ingredients of concrete for example demolishing waste as replacement of fine and coarse aggregates 15 , local sand 16 , metallurgical sludge waste as coarse aggregates 17 , improved recycled aggregates by removing impurities using air blower 18 . From the above discussion it may be observed that either the literature is silent or least work is devoted on studying the effect of type of sand on workability and compressive strength of concrete made with recycled aggregates from demolishing waste.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The X-ray diffraction (XRD) results also indicated that the Ca(OH) 2 peak showed a high density in the concrete without additives and completely disappeared with the presence of silica fume and slag. Moreover, the peak intensity of C 4 AH 13 sharply recorded with silica fume and granular slag (Tebbal and Rahmouni, 2016). Behim et al (2002) also claimed in their research that the size of crystallization and particle size of the slag plays an important role in the potential development of the mechanical resistance of the mortar, as the grinding has two factors: smoothness and also the surface stimulation through the creation of defects.…”
Section: Introductionmentioning
confidence: 97%
“…The X-ray diffraction (XRD) results also indicated that the Ca(OH) 2 peak showed a high density in the concrete without additives and completely disappeared with the presence of silica fume and slag. Moreover, the peak intensity of C 4 AH 13 sharply recorded with silica fume and granular slag (Tebbal and Rahmouni, 2016).…”
Section: Introductionmentioning
confidence: 99%